Prospective optical motion correction for 3D time‐of‐flight angiography. Issue 6 (10th August 2012) - Kopeinigg, Daniel; Aksoy, Murat; Forman, Christoph; Straka, Matus; Seaman, Danielle; Rosenberg, Jarrett; Fleischmann, Dominik; Hornegger, Joachim; Bammer, Roland
Abstract: Magnetic resonance angiograms are often nondiagnostic due to patient motion. In clinical practice, the available time to repeat motion‐corrupted scans is very limited—especially in patients who suffer from acute cerebrovascular conditions. Here, the feasibility of an optical motion correction system to prospectively correct patient motion for 3D time‐of‐flight magnetic resonance angiography was investigated. Experiments were performed on five subjects with and without parallel imaging (SENSE R = 2) on a 1.5 T unit. Two human readers assessed the data and were in good agreement (kappa: 0.77). The results from this study indicate that the optical motion correction system greatly reduces motion artifacts when motion was present and did not impair the image quality in the absence of motion. Statistical analysis showed no significant difference between the (vendor‐provided) SENSE and the nonaccelerated acquisitions. In conclusion, the optical motion correction system tested in this study has the potential to greatly improve 3D time‐of‐flight angiograms regardless of whether it is used with or without SENSE. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.